IMPLEMENTATION OF STEM-BASED DIGITAL TRANSFORMATION TO IMPROVE SCIENCE LITERACY OF JUNIOR HIGH SCHOOL STUDENTS IN PADANGSIDIMPUAN CITY - Nasution, Nurhidaya Fithriyah; Nasution, Febriani Hastini; Harahap, Muhammad Syahril (Universitas Tanjungpura, 2026)
The low level of science literacy among junior high school students, especially in regions such as Padangsidimpuan City, remains a major obstacle to delivering education that meets the demands of the 21st century. Digital transformation, combined with the STEM (Science, Technology, Engineering, and Mathematics) approach, is considered a promising solution by integrating technology into instruction and enhancing students